Study of the imperatives of promoting financial inclusion in Iraq: Opportunities and challenges (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to provide an analytical study to promote financial inclusion in Iraq by clarifying the opportunities and challenges of the economic and demographic situation in Iraq, studying the structure of the financial system and introducing non-bank financial institutions operating in Iraq, and using the descriptive approach. Analytical in the study of the phenomenon of research, the research reached a number of conclusions, the most prominent of which were:• Iraqi society is a young society.• The majority of the population is 70 percent. They live almost in urban areas.• The coverage of bank branch networks is concentrated in only four provinces, leaving other provinces outside financial services.